Odpowiedź :
1.
(1+a)/(1-a)=b/c
stad b=c(1+a)/(1-a)
c(1+a)=b(1-a)
c=b(1-a)/(1+a)
2.
a/(b-2)=c/(b+2)
a=c(b-2)/(b+2)
a(b+2)=c(b-2)
ab+2a=bc-2c
ab-bc=-2c-2a
b(a-c)=-2(c+a)
b=-2(c+a)/(a-c)
(1+a)/(1-a)=b/c
stad b=c(1+a)/(1-a)
c(1+a)=b(1-a)
c=b(1-a)/(1+a)
2.
a/(b-2)=c/(b+2)
a=c(b-2)/(b+2)
a(b+2)=c(b-2)
ab+2a=bc-2c
ab-bc=-2c-2a
b(a-c)=-2(c+a)
b=-2(c+a)/(a-c)
1+a / 1-a = b/c
b
b=c+ac / 1-a
c
1+a / 1-a = b / c
c+ac / 1-a = b
b-ab = c+ac
b-ab / a = 2c
c= b-ab / a²
b)
a / b-2 = c / b+2
a
a = c / b²-4
b
a / b²-4 = c
a=b²c-4c
b²=a / -3c
b= √a / √-3c
b
b=c+ac / 1-a
c
1+a / 1-a = b / c
c+ac / 1-a = b
b-ab = c+ac
b-ab / a = 2c
c= b-ab / a²
b)
a / b-2 = c / b+2
a
a = c / b²-4
b
a / b²-4 = c
a=b²c-4c
b²=a / -3c
b= √a / √-3c